2006
DOI: 10.1097/01.mao.0000199758.74685.2c
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Hearing Loss from Semi-Circular Canal Transection in Pseudomonas Otitis Media with Ciprofloxacin-Dexamethasone Irrigation

Abstract: Irrigation of the guinea pig bulla with cipro-dex following SCT in the setting of PA OM appears safe and may yield beneficial effects on hearing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A recent study in guinea pigs found that ears with transected semicircular canal (TSC) treated with cipro-dex showed a mean click threshold improvement of 4.6 dB from pre-transection to 7-10 days post-transection, whereas thresholds in the SCT ears treated with saline worsened by 7.5 dB [30].…”
Section: Discussionmentioning
confidence: 98%
“…A recent study in guinea pigs found that ears with transected semicircular canal (TSC) treated with cipro-dex showed a mean click threshold improvement of 4.6 dB from pre-transection to 7-10 days post-transection, whereas thresholds in the SCT ears treated with saline worsened by 7.5 dB [30].…”
Section: Discussionmentioning
confidence: 98%
“…The relative anti-inflammatory activity of dexamethasone is $25-fold greater than that for cortisol (hydrocortisone) and $7-fold greater than that for prednisolone or prednisone [8]. Currently, most of the information available concerning the safety of steroids in the human middle ear is derived from animal data [6,[9][10][11], and a few ototopical [12][13][14] and intratympanic [15] studies in humans.…”
mentioning
confidence: 97%